A Value Model for Asset Tracking Technology to Support Naval Sea-Based Resupply. Issue 2 (2nd April 2016) - Scala, Natalie M.; Pazour, Jennifer A.
Abstract: A value model is developed for military logistics that fulfill emergent requests for tailored resupply packages from the sea. Asset tracking technologies, including radio frequency identification, barcoding, internal positioning systems (IPS), and camera-aided technology, are considered as alternatives to a multi-objective decision model. Model measures include registration of inventory in the system, stowage factor enablement, storage location precision, retrieval identification accuracy, system compatibility, and security. The decision model is presented using insights from subject matter experts. Given the requirements of selective offloading in dense storage environments, IPS is the preferred asset tracking technology. Sensitivity analysis and recommendations for engineering managers are provided.